Brief Report: HIV Testing Among Pregnant Women Who Attend Antenatal Care in Malawi. (15th August 2015) - Tenthani, Lyson; Haas, Andreas D.; Egger, Matthias; van Oosterhout, Joep J; Jahn, Andreas; Chimbwandira, Frank; Tal, Kali; Myer, Landon; Estill, Janne; Keiser, Olivia
Abstract : Abstract: Malawi adopted the Option B+ strategy in 2011. Its success in reducing mother-to-child transmission depends on coverage and timing of HIV testing. We assessed HIV status ascertainment and its predictors during pregnancy. HIV status ascertainment was 82.3% (95% confidence interval: 80.2 to 85.9) in the pre-Option B+ period and 85.7% (95% confidence interval: 83.4 to 88.0) in the Option B+ period. Higher HIV ascertainment was independently associated with higher age, attending antenatal care more than once, and registration in 2010. The observed high variability of HIV ascertainment between sites (50.6%–97.7%) and over time suggests that HIV test kit shortages and insufficient numbers of staff posed major barriers to reducing mother-to-child transmission.